Heading into trouble: A comparison of the Latin American crises and the Euro area's current crisis - Manuel Ramos-Francia; Ana María Aguilar-Argaez; Santiago García-Verdú; Gabriel Cuadra (Banco de México, 2014)
We compare the experience of Latin American external debt crises, in particular the one in the 80s, with the current European one. We do so with the aim of shedding some light on the needed adjustment mechanisms. We argue for the need of much larger debt relief in Europe. To address the moral hazard problems that would arise, we propose providing such relief conditional on the reduction of both the fiscal and the current account deficits to zero as a commitment signal.
Keywords: F34; H12; H63; 330; Sovereign Debt; Debt Crisis; Crisis Management